Structures and Properties of Rubberlike Networks. - Erman, Burak (Oxford University Press, 1997)
Rubber elasticity is an important sub-field of polymer science. This book is a sequel to the authors' previous, introductory book, "Rubberlike Elasticity: A Molecular Primer" (1988). It also places strong emphasis on molecular concepts and theories, and on equilibrium properties.